2021
DOI: 10.3390/ijerph18115868
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes in South Africa: A Systematic Review and Meta-Analysis

Abstract: Synthesis of existing prevalence data using rigorous systematic review methods is considered an effective strategy to generate representative and robust prevalence figures to inform health planning and policy. The purpose of this systematic review was to identify, collate, and synthesise all studies reporting the prevalence of total and newly diagnosed type 2 diabetes (T2DM), impaired glucose tolerance (IGT), and impaired fasting glucose (IFG) in South Africa. Four databases, PubMed, Scopus, Web of Science, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…This is especially true for hypertension, which is reported to have a higher prevalence in the country (46% women and 44% men) vs. 14% in this survey ( 42 ). Similarly, our estimate for diabetes was 4%, while a recent systematic review reported the prevalence of diabetes in South Africa to be close to 15% for people aged 25 years and older ( 43 ). The lower multimorbidity prevalence may be linked to how questions about self-reported disease conditions were asked.…”
Section: Discussionsupporting
confidence: 69%
“…This is especially true for hypertension, which is reported to have a higher prevalence in the country (46% women and 44% men) vs. 14% in this survey ( 42 ). Similarly, our estimate for diabetes was 4%, while a recent systematic review reported the prevalence of diabetes in South Africa to be close to 15% for people aged 25 years and older ( 43 ). The lower multimorbidity prevalence may be linked to how questions about self-reported disease conditions were asked.…”
Section: Discussionsupporting
confidence: 69%
“…The limited national data on FPG and the prevalence of diabetes in South Africans [11] meant that we had to model estimates from the few available national surveys and some small-area studies that used different methods to identify individuals with high FPG and diabetes (Table 1, and Table S1 in the appendix: https://www.samedical.org/ file/1846). The model allowed for differences by population group, with urban and rural categories for black Africans to allow for changes in urbanisation in this group during the study time period; other population groups had high urban proportions throughout the period.…”
Section: Researchmentioning
confidence: 99%
“…The country is faced with a growing burden of HBP, concurrent with a rapid increase of T2D (i.e., raised glucose levels), another major source of morbidity and mortality, collectively owing to epidemiological transition, poor diets and inactive lifestyle [32][33][34]. T2D pooled prevalence of 15.25% has been reported in South Africans aged 25 years and older, irrespective of certain demographic factors, as well as diagnostic test and study design [35]. T2D and HBP overlap in the population and in most cases, the advancement of hypertension and T2D advance with time [26].…”
Section: Introductionmentioning
confidence: 99%